Epigenetic analysis suggests aberrant cerebellum brain aging in old-aged adults with autism spectrum disorder and schizophrenia - Liu, Li; Qi, Xin; Cheng, Shiqiang; Meng, Peilin; Yang, Xuena; Pan, Chuyu; Zhang, Na; Chen, Yujing; Li, Chune; Zhang, Huijie; Zhang, Zhen; Zhang, Jingxi; et al. (Molecular psychiatry, 2023)
The aberrant aging hypothesis of schizophrenia (SCZ) and autism spectrum disorder (ASD) has been proposed, and the DNA methylation (DNAm) clock, which is a cumulative evaluation of DNAm levels at age-related CpGs, could serve as a biological aging indicator. This study evaluated epigenetic brain aging of ASD and SCZ using Horvath’s epigenetic clock, based on two public genome-wide DNA methylation datasets of post-mortem brain samples (N ASD = 222; N SCZ = 142). Total subjects were further divided into subgroups by gender and age. The epigenetic age acceleration ( AgeAccel ) for each sample was calculated as the residual value resulting from the regression model and compared between groups. Results showed DNAm age has a strong correlation with chronological age in both datasets across multiple brain regions ( P < 0.05). When divided into equally sized age groups, the AgeAccel of the cerebellum (CB) region from people over 45 years of age was greater compared to the control sample ( AgeAccel of ASD vs control: 5.069 vs −6.249; P < 0.001). And a decelerated epigenetic aging process was observed in the CB region of individuals with SCZ aged 50–70 years ( AgeAccel of SCZ vs control: −3.171 vs 2.418; P < 0.05). However, our results showed no significant difference in AgeAccel between ASD and control groups, and between SCZ and control groups in the total and gender-specific groups ( P > 0.05). This study’s results revealed some evidence for aberrant epigenetic CB brain aging in old-aged patients with ASD and SCZ, indicating a different pattern of CB aging in older adults with these two diseases. However, further studies of larger ASD and SCZ cohorts are necessary to make definitive conclusions on this observation.